The special issue on FDI and multinational corporations: An introduction - Philipp Harms; Konstantin M. Wacker (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
This paper offers an introduction to the special issue on FDI and multinational corporations: http://www.economics-ejournal.org/special-areas/special-issues/fdi-and-multinational-corporations. It summarizes the contents of the five papers included, and relates them to the recent literature on the subject.
Keywords: F21; F23; 330; foreign direct investment; multinational corporations